2022
DOI: 10.1155/2022/5918826
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Context Awareness and Ubiquity on Mobile Government Service Adoption

Abstract: Context awareness and mobile factor ubiquity are considered key factors when it comes to mobile technology development and diffusion. Context is vital in interactive applications particularly when the context of users changes frequently and rapidly in the environment of handheld-mobile and ubiquitous technology systems. The understanding of the context and ubiquity in the development and diffusion of mobile government can influence the delivery of efficient public services. Mobile context-aware computing syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 169 publications
1
11
0
Order By: Relevance
“…The role that government APPs play in improving the quantity and quality of public-service delivery includes: 1) Improving public-service convenience. Due to their mobility, government APPs enable citizens to obtain ubiquitous services that traditional e-government cannot provide (Mensah & Mwakapesa, 2022); 2) Improving the equity and accessibility of public-service allocation. The vast majority of people use smart phones, narrowing the digital divide between different regions and groups and enabling governments to provide users with adequate and timely information; even rural users with less developed digital skills find it easy to operate government APPs and obtain services (Liu et al, 2014); 3) Improving the personalization and accuracy of public services.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The role that government APPs play in improving the quantity and quality of public-service delivery includes: 1) Improving public-service convenience. Due to their mobility, government APPs enable citizens to obtain ubiquitous services that traditional e-government cannot provide (Mensah & Mwakapesa, 2022); 2) Improving the equity and accessibility of public-service allocation. The vast majority of people use smart phones, narrowing the digital divide between different regions and groups and enabling governments to provide users with adequate and timely information; even rural users with less developed digital skills find it easy to operate government APPs and obtain services (Liu et al, 2014); 3) Improving the personalization and accuracy of public services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies have focused primarily on the initial use, acceptance, and adoption of e-government services. Most of these studies have used technology-adoption models, including the theory of reasoned action, the diffusion of innovations, TAM, the theory of planned behavior, the unified theory of the acceptance and use of technology, and the e-government adoption model, to explore factors that predict the initial adoption of government APPs (Ahmad & Khalid, 2017; Creutzberg et al, 2023; Hung et al, 2013; Liu et al, 2014; Mensah & Mwakapesa, 2022; Sharma et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to a lack of a domestic ICT industry, several developing countries import ICT. Researchers have implicated strategic, technological, policy, and organizational factors in this issue (Mensah & Mwakapesa, 2022). There are a variety of legal, political, social, and economic obstacles that prevent developing countries from fully utilizing e-government; this led to the development of mobile government (Karadimas et al, 2008;Wirtz & Birkmeyer, 2018).…”
Section: Challenges To M-government Adoption In Developing Countriesmentioning
confidence: 99%
“…It was found that performance expectancy was the primary criterion which influence retailers' behavioral intention to adopt mobile payment apps [39]. The studies [40][41][42][43][44][45][46][47] have also studied the relationship between performance expectancy and behavioral intention. With this backdrop, the following hypotheses were formed: H1: there is no impact of performance expectancy on behavioural intention to use mobile payment applications.…”
Section: Introductionmentioning
confidence: 99%
“…In research conducted by Alshare and Lane [55], it was revealed that there is a strong relationship between effort expectancy and the behavioral intention of customers. The studies [40][41][42][43][44][45][46][47] have also evaluated the relationship between effort expectancy and behavioral intention. The above discussion led to the formulation of the following hypothesis: H2: there is no impact of effort expectancy on behavioral intention to use mobile payment applications.…”
Section: Introductionmentioning
confidence: 99%